A day in the life: Interviews with three PE/VC librarians. Issue 3 (2nd October 2017) - Southard, Doug
ABSTRACT: This article is an interview with three librarians with extensive experience in private equity (PE) and venture capital (VC) research. Two of the participants work in a business research consultancy and one works in an academic library within a graduate business school. They shared their thoughts on what is unique or noteworthy about conducting research in these areas. Topics covered include: a typical workday; common research requests; information resources used; differences in research in private equity and venture capital; the information needs of entrepreneurs, students and professors; and challenges that arise in conducting PE and VC research.